Deterioration mechanism and stochastic damage modeling of tunnel lining concrete in hydrothermal corrosive environments - Yu Ning; Zhiwei Yan; Yanhua Zeng; Chunwei Zhang; Yucang Dong (Scientific Reports)
Abstract Corrosion caused by geothermal water and thermal damage due to high temperature are the critical causes of lining material cracking and structural instability in hydrotherm al high-geothermal tunnels. In order to investigate the coupled effect of high temperature and corrosion on the macroscopic mechanical properties and microstructure of lining concrete, a series of experiments have been conducted, and a new thermal-corrosion damage model has been proposed that can describe the evolution of the mechanical properties of concrete in this particular environment. The study results indicate that the mass loss rate exhibits a trend of decreasing and then increasing as the degree of corrosion increases. It has been demonstrated that elevated temperatures can significantly accelerate the corrosion of concrete by sulfate ions, with a mass loss rate exceeding 15% observed at 60 °C–120 d. The corrosion of concrete at elevated temperatures also results in internal expansion and damage, accompanied by a notable increase in the number and size of cracks. The compressive strength and elasticity modulus of specimens decline with an increase in temperature and an extension of corrosion time. The maximum reduction in intensity is 68%. The simulation results based on the discrete-random damage model proposed in this paper are able to characterise the anisotropic properties of concrete under high-temperature and corrosive conditions. In comparison to the conventional discrete element model parameter calibration method, the crack spreading and damage patterns of specimens exhibit notable discrepancies. The degree of fragmentation at the damage area intensified considerably with the alteration of temperature and corrosion duration, accompanied by a reduction in the number of medium-sized fragments. There is a downward trend in the number of cracks under the destruction ultimate state. The research findings offer theoretical guidance for the resistance degradation of concrete structures in service under hydrothermally corrosive environments and structural analysis.